Legal Protection of Indonesia’s Fisheries from Foreign Investment: A Social-State Approach - Ida Hanifah; Hariyanto Hariyanto; Lilawati Ginting; Ismail Koto; Rizka Syafriana (Jurnal IUS Kajian Hukum dan Keadilan, 2026)
The fisheries sector is at the criticality of Indonesia’s maritime sovereignty, economic resilience and coastal communities’ livelihood security. Simultaneously, the increase in foreign investments on marine and fisheries activities has aroused big apprehensions over resource depletion, inequality in profit sharing as well as diminishing power of small-scale fishers. This is further complicated by Indonesia’s overlapping legal regimes, particularly the Fisheries Law and the Investment Law, as well as international ones such as UNCLOS. This study focuses on the legal protection in Indonesia regarding the fisheries sector affected by foreign investment, to see from normative and scientific perspectives. It also aims to offer directions for how regulatory reform can be shaped through a social-state perspective. The study with semi-structure qualitative descriptive method use Systematic Literature Review (SLR) followed by bibliometric analysis using VOSviewer and PRISMA mapping. Initially, 128 articles published from 2021 to 2025 underwent a screening process by following the Global PRISMA model as per meta-analysis standards; finally, 20 articles met the final inclusion criteria. Results indicate that ongoing discourses are still mostly governed by technocratic and punitive law-making processes. Thus, little attention is paid to the legal re-establishment in accordance with principles of distributive justice, ecological sustainability and effective involvement of the community. Regulatory gaps arise from unclear legal protection for small-scale fishers, and poor integration of the fisheries policy within the broader across marine governance framework. These gaps have resulted in fragmented protection and unequal benefit sharing from fish resources of Indonesia. This research advocates for a state–based regulatory model which empowers the state to act more strongly as both protector and distributor of maritime goods. This framework should be centered on issues of ecological justice, rigorous control over foreign investment, and an increased role for coastal communities in governance of fisheries. The research effort aids the creation of equitable, participatory, and sustainable legal policies for marine and fisheries in Indonesia.